TO INCREASE THE EFFECTIVENESS OF TREATMENT OF PURULENT-INFLAMMATORY DISEASES OF THE FACIAL JAW AREA WITH MODERN BINDING AGENTS (International Bulletin of Medical Sciences and Clinical Research, 2024)
The article discusses the importance of using new pedagogical methods in physical education classes and the advantages of physical education classes in the formation of a healthy lifestyle.